Inter- and intraclass correlations for three standard foot radiographic measurements for plantar surface angles. Which measure is most reliable?. Issue 5 (October 2019) - Hohmann, Erik; Myburgh, Jolandie; Keough, Natalie; Tetsworth, Kevin; Glatt, Vaida
Highlights: Intra- and inter-class correlations for three commonly used for plantar surface angles were high. For intra-and inter-class correlations the length-height index is the most reliable variable. LHI represents the best, most reliable, and reproducible measure of arch height. Calcaneal and calcaneal pitch angle were only of moderate value because of observer error. Abstract: Background: The purpose of this study was to evaluate the reliability and reproducibility of three commonly used radiographic measures for plantar surface angles. Methods: The calcaneal angle (CA), calcaneal pitch angle (CPA), and length-height index (LHI) was measured by three independent examiners on two occasions on lateral foot radiographs. Intra- and inter-rater correlations were calculated using a general linear estimate model and post-hoc tests for repeated measures. Bland–Altman's plots with limits of agreement were used for observer differences in scores. Results: The intra-class correlations for the CA ranged from 0.91 to 0.94, for the CPA from 0.93 to 0.98, and for the LHI from 0.96 to 0.97. The inter-class correlations were 0.80 for CA, 0.83 for CPA and 0.93 for LHI. Conclusions: The results of this study strongly suggest that the length-height index was the most consistent and reliable measure for arch height. Level of evidence: Diagnostic Level II, validity.